2016
DOI: 10.1080/2162402x.2016.1208878
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase 2 is involved in the pro-tumorigenic potential of γδ17 T cells in melanoma

Abstract: ABSTRACTgd T lymphocytes may exert either protective or tumor-promoting functions in cancer, mostly based on their polarization toward interferon (IFN)-g or interleukin (IL)-17 productions, respectively. Here, we demonstrate that gd T cells accelerate the spontaneous metastatic melanoma development in a model of transgenic mice for the human RET oncogene (Ret mice). We identify unanticipated roles of inducible nitric oxide synthase (NOS2) in favoring the recruitment of pro-tumor gd T cells within the primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…We have recently shown that NOS2 improves the recruitment of γδ T cells within the tumor microenvironment in a murine model of spontaneous melanoma [27]. Here we wondered whether NOS2 also impacts γδ T cell proportions at steady state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that NOS2 improves the recruitment of γδ T cells within the tumor microenvironment in a murine model of spontaneous melanoma [27]. Here we wondered whether NOS2 also impacts γδ T cell proportions at steady state.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we detected NOS2 expressing γδ T cells within the primary tumor of melanoma patients, but also in the primary tumor and tumor draining LNs in mice transgenic for the Ret oncogene developing a spontaneous metastatic melanoma (model Ret) [27]. γδ T cells in Ret mice lysed less efficiently tumor cells, and produced less IFN-γ than their counterparts in Ret mice deficient for NOS2.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS expression regulation varies depending on cell types and species (30, 41). In myeloid cells, particularly in macrophages, TNFα and LPS/TLR ligands-activated NF-κB is a major regulator of iNOS expression (27, 28, 42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression regulation of iNOS has been extensively studied in various types of cells, including myeloid cells in vitro (2730), the molecular mechanism underlying iNOS expression regulation in tumor-induced MDSCs is essentially unknown. We report here that the histone methyltransferase SETD1B regulates trimethylation of histone H3 lysine 4 (H3K4Me3) at the nos2 promoter to activate iNOS expression in tumor-induced MDSCs.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 NOS2 is primarily regulated at the expression 37 leading to various outcomes during infection. [38][39][40] In melanoma, NOS2 activation in γδT cells promoted dissemination in mouse melanoma models 41 and was associated with poor survival in melanoma patients. 30 Therefore, we examined whether NOS2/iNOS would be associated with ulceration and chronic inflammation in our cohorts.…”
Section: No Relevance Of Other Key Molecules Involved In Scavenging Amentioning
confidence: 99%